The Litany of an Independent West African Church - Turner, Harold W. (Practical anthropology, 1960)
A promising new small periodical called the Sierra Leone Bulletin of Religion appeared in 1959. Of special interest to students of religion in general and of Africa in particular, it is edited by members of the faculty of Fourah Bay College, Freetown, Sierra Leone. In order to introduce the new publication to readers of Practical Anthropology, as well as to share a valuable article with a wider audience, we reprint the present discussion of a litany developed by a separatist sect in West Africa.